The Serotonin-6 Receptor as a Novel Therapeutic Target - 윤형문; 임혜원 (한국뇌신경과학회, 2011)
Serotonin (5-hydroxytryptamine, 5-HT) is an important neurotransmitter that is found in both the central and peripheral nervous systems. 5-HT mediates its diverse physiological responses through 7 different 5-HT receptor families: 5-HT1, 5-HT2, 5-HT3, 5-HT4, 5-HT5, 5-HT6, and 5-HT7 receptors. Among them, the 5-HT6 receptor (5-HT6R) is the most recently cloned serotonin receptor and plays important roles in the central nervous system (CNS) and in the etiology of neurological diseases. Compared to other 5-HT receptors, the 5-HT6R has been considered as an attractive CNS therapeutic target because it is expressed exclusively in the CNS and has no known isoforms. This review evaluates in detail the role of the 5-HT6R in the physiology and pathophysiology of the CNS and the potential usefulness of 5-HT6R ligands in the development of therapeutic strategies for the treatment of CNS disorders. Preclinical studies provide support for the use of 5-HT6R ligands as promising medications to treat the cognitive dysfunction associated with Alzheimer’s disease, obesity, depression, and anxiety.